THE EFFECT OF SAVINGS PRODUCT KNOWLEDGE, MOTIVATION AND FACILITIES ON THE DECISION TO SAVING AT PT.BPR DHARMA NAGARI - dika, handika; Purwanto, Kelik; Wiska, Mayroza (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study was conducted to determine the effect of knowledge of savings products, motivation and facilities on saving decisions at PT. BPR Dharma Nagari. The purpose of this study was to determine and analyze the effect of knowledge of savings products, motivation and facilities on saving decisions at PT. BPR Dharma Nagar. This study uses a quantitative method with data collection using a questionnaire. Data analysis techniques with validity tests, reliability tests, multiple linear regression analysis, classical adjustion tests, t tests, f tests, determination tests (R2 ) . The population in this study was 436 respondents for the year 2022/2023 and 209 samples were used